Long-Lived Charge Carriers in Mn-Doped CdS Quantum Dots for Photoelectrochemical Cytosensing - Wu, Peng; Pan, Jian-Bing; Li, Xiang-Ling; Hou, Xiandeng; Xu, Jing-Juan; Chen, Hong-Yuan (Chemistry : a European journal, 2015)
Photoelectrochemical (PEC) biosensing with semiconductor quantum dots (QDs) has received great attention because it integrates the advantages of both photo‐excitation and electrochemical detection. During the photon‐to‐electricity conversion in PEC processes, electron–hole (charge) separation competes with electron–hole recombination, and the net effect essentially determines the performance of PEC biosensors. Herein, we propose a new approach for slowing down electron–hole recombination to increase charge separation efficiency for PEC biosensor development. Through doping with Mn2+, a pair of d bands (4T1 and 6A1) is inserted between the conduction and valence bands of CdS QDs, which alters the electron–hole separation and recombination dynamics, allowing the generation of long‐lived charge carriers with ms‐scale lifetime that decay about 104–105‐fold more slowly than in the case of undoped QDs. Photocurrent tests indicated that Mn2+ doping resulted in an approximately 80 % increase in photocurrent generation compared with undoped CdS QDs. For application, the Mn‐doped CdS QDs were coated on the surface of a glassy carbon electrode and functionalized with a cell surface carbohydrate‐specific ligand (3‐aminophenylboronic acid). In this way, a sensitive cytosensor for K562 leukemia cells was constructed. Moreover, the sugar‐specific binding property of 3‐aminophenylboronic acid allowed the electrode to serve as a switch for the capture and release of cells. This has been further explored with a view to developing a reusable PEC cytosensing platform. Impeded recombination for enhanced separation: Long‐lived charge carriers elicited by Mn2+ doping of CdS quantum dots (QDs) boost photocurrent generation therein (see figure). This enhancement has been exploited for photoelectrochemical cytosensing.